2020
DOI: 10.1021/acs.energyfuels.0c02743
|View full text |Cite
|
Sign up to set email alerts
|

Study of Very High Molecular Weight Cluster Presence in THF Solution of Asphaltenes and Subfractions A1 and A2, by Gel Permeation Chromatography with Inductively Coupled Plasma Mass Spectrometry

Abstract: Super high-molecular-weight (SHMW) asphaltene aggregates, hereafter called asphaltene clusters, have been observed for the first-time using gel permeation chromatography with inductively coupled plasma mass spectrometry (GPC-ICP HR MS). Presumably these clusters are composed by nanoaggregates joined by physical interactions such as polar and dispersion forces. These clusters were observed for three asphaltenes samples (Hamaca, Cerro Negro and Boscan) and in their corresponding subfractions, A1 (insoluble in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 60 publications
5
40
0
Order By: Relevance
“…As reported in previous studies [18,27,28], GPC-ICP HR MS analyses were performed using a Thermo Scientific Element XR sector field ICP HR MS instrument that operates at a resolution of 4000 (medium resolution) to access spectrally interfered isotopes of 58 Ni, 32 S, and 51 V. The spectrometer was equipped with a Fassel-type quartz torch shielded with a grounded Pt electrode and a quartz injector (1.0 mm i.d.). A Pt sampler (1.1-mm orifice diameter) and a Pt skimmer (0.8-mm orifice diameter) were used.…”
Section: Gpc-icp Hr Ms Analysismentioning
confidence: 99%
“…As reported in previous studies [18,27,28], GPC-ICP HR MS analyses were performed using a Thermo Scientific Element XR sector field ICP HR MS instrument that operates at a resolution of 4000 (medium resolution) to access spectrally interfered isotopes of 58 Ni, 32 S, and 51 V. The spectrometer was equipped with a Fassel-type quartz torch shielded with a grounded Pt electrode and a quartz injector (1.0 mm i.d.). A Pt sampler (1.1-mm orifice diameter) and a Pt skimmer (0.8-mm orifice diameter) were used.…”
Section: Gpc-icp Hr Ms Analysismentioning
confidence: 99%
“…To go further and complete this study, future simulations may investigate solvent effects by considering a solvent such as THF. Indeed, a recent study 41 suggests the formation and characterizes very high molecular weight clusters of asphaltene from subfractions A1 and A2.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The complex nature of asphaltenes has been extensively researched, and their characterization has been the subject of many studies using different techniques. After early work on gel permeation chromatography (GPC) inductively coupled plasma atomic emission spectroscopy by Reynolds et al that have shown a trimodal distribution of vanadium compounds in asphaltene, recent results with the same separation technique but hyphenated with inductively coupled plasma high-resolution mass spectrometry (GPC-ICP-HR-MS) and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) demonstrate that asphaltenes are composed of low- to medium-, medium-, high- and superhigh-molecular-weight fractions, meaning that, by nature, asphaltenes form families of aggregates of different hydrodynamic volumes in solution. This result can have an important impact on the understanding of asphaltene adsorption processes and may be the key to discerning the dynamics of the process.…”
Section: Introductionmentioning
confidence: 99%